La modulation sociale de la voix ne compromet pas le mécanisme de phenotype matching chez le mandrill - Florence Levréro; Greta Carrete-Vega; Anais Herbert; Ismaël Lawabi † 2015; Alexandre Courtiol; Eric Willaume; Peter M. Kappeler; Marie J.E. Charpentier (Revue de Primatologie)
Kin selection theory provides a strong theoretical framework to explain the evolution of altruism and cooperative behaviour among genetically related individuals. However, the proximate mechanisms underlying kin discrimination, a necessary process to express kin-related behaviour, remain poorly known. In particular, no study has yet unambiguously disentangled mechanisms based on learned familiarity from true phenotype matching in kin discrimination based on vocal signals. Here we show that in addition to genetic background, social accommodation also shapes individual voices in an Old World monkey (Mandrillus sphinx), even though primate vocalizations were thought to be innate and little flexible. Nonetheless, social shaping of voice parameters does not impair kin discrimination through phenotype-matching of unknown relatives, revealing unexpected discriminatory versatility despite signal complexity. Accurate signal production and perception, therefore, provide a basis for kin identification and kin-biased behaviour in an Old World primate.